Tracking Dynamic Phase Segregation in Mixed‐Halide Perovskite Single Crystals under Two‐Photon Scanning Laser Illumination. Issue 11 (23rd May 2019) - Chen, Weijian; Mao, Wenxin; Bach, Udo; Jia, Baohua; Wen, Xiaoming
Abstract: Photoinduced phase segregation in mixed halide perovskites has received considerable attention due to its critical roles in diminishing device performance in photovoltaic and light‐emitting applications. Here, dynamic photoinduced phase segregation and dark recovery in mixed halide perovskite single crystal microplatelets are investigated, combining depth‐resolved, temporal‐resolved, and detection‐wavelength selective spectroscopic imaging techniques. Under identical illumination, the edges and interior of microplatelets exhibit significantly different phase segregation. An intimate correlation of PL dynamics between I‐phase and Br‐phase indicates that the halide substitution is the dominant effect. In the dark, the phase‐segregated crystals reversibly recover to the stable equivalence. This work clarifies the critical role of the edge state of the microplatelets and reveals the physical mechanism of phase segregation in mixed halide perovskites, which is of crucial importance for their applications in photovoltaics and photonics. Abstract : Photoinduced phase segregation and dark recovery in mixed halide perovskite single crystal microplatelets are investigated, combining depth‐resolved, temporal‐resolved, and detection‐wavelength selective spectroscopic imaging techniques, where the edges and interior of microplatelets exhibit significantly different phase segregation.